UI TESTING WITH PUPPETEER implement end-to-end testing and browser automation using javascript... and node.js. - KONDRATIUK, DARIO (PACKT PUBLISHING LIMITED, 2021)
Explore Google's open source web automation library Puppeteer to perform tasks such as end-to-end testing, performance monitoring, and task automation with ease. Using real-world use cases, this book will help you learn the capabilities and best practices of Puppeteer to take your automation code to the next level.